Top–Down Cognitive Control in Students with a Rigid Set-on Facial Expression - Cheremushkin, E; Petrenko, N (KnE Life Sciences, 2018)
Top–down cognitive control was studied in students by the model of fixed set for facial expression. In subjects with errors in the set fixing, it is weakened to the greatest extent. The hypothesis about the influence on the top–down cognitive control of the functional state of subjects caused by signs of autonomic dysfunction, personal anxiety, depression and sleep quality is considered. Keywords: top–down cognitive control, emotional facial expression, errors recognition, EEG, alpha oscillations